THE DEVELOPMENT STRATEGY OF NATIVE CHICKEN (AYAM KAMPUNG) INDUSTRY IN JEMBER REGENCY USING SWOT ANALYSIS - Nanang Dwi Wahyono; Merry Muspita Dyah Utami (UNEJ e-Proceeding, 2017)
The aim of the study to analyze the strengths, weaknesses, opportunities, and threats (SWOT) todevelop strategy of native chicken (ayam kampung) industry in Jember Regency. The study wasconducted from April to October 2016. The method was descriptive analysis method, usingquestionaires, interviews, and observations. Methods of data analysis using the SWOT analysiswere used to identify the internal environmental factors (strengths and weaknesses) andexternal environmental factors (opportunities and threats) areas, internal-external (IE Matrix),and SWOT Matrix. The result was then drawn in the quadrant analysis of SWOT andinterpreted in the SWOT matrix show the position and alternative strategies that can be run.The result showed that internal identified total score was 0.441 and external identified totalscore was 0.0897. The development strategy native chicken (ayam kampung) by aggressivegrowth strategy in quadrant I. Strategy that can be used is maintaining on going activitieshowever its quantity and quality remains developed. There are five alternative strategiesresulted to develop native chicken (ayam kampung) industry in Jember Regency and thepriority strategy is to optimize the role of agribusiness subsystem.